Agricultural trade: What Matters in the Doha Round? - Laborde Debucquet, David; Martin, Will (International Food Policy Research Institute, 2013)
In this paper, we provide an overview of the agricultural trade negotiations within the current World Trade Organization (WTO) negotiations and we show that including agriculture in the Doha Development Agenda talks is important both economically and politically, although the political resistance to reform is particularly strong in this sector.